Black Knot Unraveled: Phenotypic Characterization of Disease Resistance in Japanese Plums - Chloe Shum; Wendy McFadden-Smith; Walid El Kayal; Jayasankar Subramanian (Horticulturae)
Black knot (BK) disease, caused by Apiosporina morbosa (Schwein.) v. Arx, significantly afflicts Japanese plums (Prunus salicina L.), resulting in substantial economic losses due to its destructive invasion of branches and trunks. Phenotyping for disease severity is critical to understanding resistance and susceptibility across diverse genotypes. In this study, 200 Japanese plum trees from a mixed lineage breeding program were phenotyped for BK severity using a rating scale from 0 to 5. Trees were rated by two independent raters and repeated on a second day, in early spring 2023, before leaf emergence, for peak visibility. The rating system was designed to capture varying levels of infection, with 0 representing no symptoms and 5 indicating severe infection with major effects to the tree’s overall health. Compared to data from 2015 and 2018, there was a noticeable increase in the number of heavily diseased trees relative to symptom-free trees. In 2023, the proportion of completely resistant trees remained the same as in 2018, suggesting true resistance. Median scores were calculated from four independent ratings per tree, comprised of two individuals on two different days, minimizing individual biases. Additionally, inter-rater reliability was assessed using the weighted Kappa statistic, which yielded a value of 0.903, indicating strong agreement between raters. This phenotypic assessment provides a robust dataset for correlation with genetic markers and supports further breeding efforts aimed at developing BK-resistant cultivars.